EFFECT OF METHANOL EXTRACT SKIN FRUIT Mangosteen (Garcina mangostana L) ON THE GROWTH CULTURE Mycobacterium tuberculosis STRAIN EAST LOMBOK - Ariami, Pancawati; Rohmi, Rohmi (Jurnal Analis Medika Biosains (JAMBS), 2014)
AbstractMangosteen (Garcinia mangostana L) contain the highest antioxidant Xanthones, one of which is obtained by solvent extraction using methanol .Processed methanol extract of mangosteen peel have been used and proven to cure various diseases, including pulmonary tuberculosis caused by Mycobacterium tuberculosis . Research on the methanol extract of mangosteen peel against M tuberculosis is still limited , and the use of local strain Lombok Timur no . The study aimed to determine the effect of the methanol extract of mangosteen peel on the growth of M tuberculosis strains East Lombok cultured. Pre - experimental research in the laboratory using three samples of M tuberculosis strains East Lombok and controls germs M tuberculosis H37Rv , tested descriptively.Isolation mangosteen rind using methahol produce compound 12 with 6 main compound in the form of Cyclopentadecanone ,2 - hidroxy - (C15H28O2) ; 9 - octadecanoic acid (Z)-, 2-hydroxy-1-(hydroxymethyl) ethylester (CAS)-2-monoolein (C21H40O4), octadecanoic acid ( CAS ) Stearic acid ( C18H36O2 ), hexadecanoic acid ( C16H32O2 ), hexadecanoic acid , 2 - hydroxy - 1hidroxymethyl ) - ethyl ester ( CAS ) 2 - monopalmitin ( C19H38O4 ) and ( R ) - ( - ) - 14 - methyl - 8 - hexadecyn - 1 - ol ( C17H32O ) . Identify the growth of M tuberculosis results on LJ medium and M tuberculosis in Middlebrook 7H9 broth fed methanol extract of mangosteen peel grown on Middlebrook 7H10 agar. A total of two samples contained the growth of M tuberculosis (Resistant), whereas one sample was not found growing M tuberculosis (Sensitive) of the methanol extract of mangosteen peel well at concentrations of 100, 200, and 300 ug / ml.Keywords : methanol extract of mangosteen peel , culture M tuberculosis, strains East Lombok